Українські народні думи: феномен пародіювання - Коваль-Фучило, І. (Народна творчість та етнографія, 2007)
The article is about specific features of functioning of the Ukrainian national mock ballads, which originate from epic and mock traditions. The author distinguishes and analyses 4 plots of the mock ballads.